2018
DOI: 10.1007/s11276-018-1875-0
|View full text |Cite
|
Sign up to set email alerts
|

On the DoF and secure DoF of K-user MIMO interference channel with instantaneous relays

Abstract: Interference channel, in which multiple user pairs communicate over shared resources, is a building block of communications networks. Here, the K-user interference channel (IC) aided by J instantaneous relays (IRs), i.e. relays without delay, is considered. For KICJR networks, where K [ 2 and J [ 1, the DoF performance and achievable schemes have not been investigated in literature. Here, we devise a novel achievable scheme, called restricted interference alignment (RIA), which restricts the received interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The capacities of wireless networks in the presence of an IR were studied in [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. El Gamal et al, in [ 6 ], showed that in the presence of an IR, rates higher than an existing cut-set bound for a classic relay can be achieved for a point-to-point channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacities of wireless networks in the presence of an IR were studied in [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. El Gamal et al, in [ 6 ], showed that in the presence of an IR, rates higher than an existing cut-set bound for a classic relay can be achieved for a point-to-point channel.…”
Section: Introductionmentioning
confidence: 99%
“…An inner and two outer bounds were obtained. For a K -user interference channel assisted by an IR wherein the IR can only instantaneously amplify and forward a received signal in a current channel use, with the same number of antennas at all nodes, an achievable scheme and an outer bound were proposed in [ 30 ]. Though the DoF in some special cases wherein or IRs was derived, a general achievable DoF was not obtained.…”
Section: Introductionmentioning
confidence: 99%